2009
DOI: 10.3844/ajassp.2009.471.477
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan Fasting Diet Entailed a Lipid Metabolic Disorder Among Type 2 Diabetic Obese Women

Abstract: Abstract:We designed this study to assess the effect of diet during Ramadan fasting on body weight and on serum lipid components in type 2 diabetic obese women. During Ramadan of 2005, 89 diabetic women receiving oral treatment (BMI = 33.20±3.01 kg m −2 ), aged 52 (±5 years), were selected. The study was carried out over 3 periods-, before (T1: pre-fasting), during (T2: fasting), and after (T3: post-fasting) Ramadan-in Sidi-bel-Abbes city. The daily food intake during the course of 3 days was recorded, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 24 publications
(13 reference statements)
3
30
1
Order By: Relevance
“…Table 2 summarises the main characteristics of the 17 studies reporting cardiovascular risk factors. Three studies included only females [26][27][28], and one study only males [29]. The sample sizes ranged from 5 to 1301, with only three studies recruiting more than 100 participants [30][31][32].…”
Section: Association Of Ramadan Fasting On Cvd Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 summarises the main characteristics of the 17 studies reporting cardiovascular risk factors. Three studies included only females [26][27][28], and one study only males [29]. The sample sizes ranged from 5 to 1301, with only three studies recruiting more than 100 participants [30][31][32].…”
Section: Association Of Ramadan Fasting On Cvd Eventsmentioning
confidence: 99%
“…Overall 17 out of the 22 studies reported effects on glycaemic control. Five studies reported a favourable effect of fasting on glycaemic parameters [27][28][29]31,33]. These studies showed a significant reduction in glycaemic parameters ranging from 0.48% to 0.93% for HBA1c and from 0.82 to 1.6 mmol/l for blood glucose.…”
Section: Glycaemic Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cohort of 276 obese women with type 2 diabetes, fasting during Ramadan was associated with decreased total calorie intake, weight reduction [9] and improvement in glucose homeostasis [10]. Recommendations for the management of diabetes during Ramadan were last published in 2005 by the American Diabetes Association.…”
Section: Introductionmentioning
confidence: 99%
“…Herbal effects obsrved in diffirent cases (Abdel Wahab et al, 2008;Alhusseini et al, 2010;Balasubramanyam et al, 2006;Hajati et al, 2011;Khaled and Belbraouet, 2009;Mahfouz et al, 2010;Mansi, 2006;Pulakat et al, 2008;Sulaiman et al, 2009;Zhou et al, 2010).…”
Section: Introductionmentioning
confidence: 99%